The Role of Public Relations Team: Case Study of Image Management in the Governor of Central Java, Ganjar Pranowo in the Digital Era - Putra, Novian Anata; Raharjo, Ema Oktoviani (Jurnal Pekommas, 2020)
Digital era forced public relations to manage the images in new ways. As a result, they could not rely only on the management of mass media. The impulse of media convergence influences a shift in political communication. Ganjar Pranowo became one of the governors who manage their image with all the changes from this era of convergence. Even though Ganjar is the head of government, his image is not only managed by government public relations. Bagian Humas Provinsi Jawa Tengah is one of the section which takes the smallest part in managing the image of Ganjar Prabowo. There are two other teams formed at the initiation of Ganjar to manage its image. A qualitative research with case study method will conducted in this research. The aim of this research is to describe the image management of Ganjar Pranowo in the digital era.  The results show clearly that government public relations is still unable to work alone. But if you look at the collaboration performance of the three teams, this image manager is at the ideal level. In addition, the role of data is the main key in its management.